2016
DOI: 10.3844/ajavsp.2016.70.84
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Hydatid Disease (Cystic Hydatidosis) in Libya: A review

Abstract: Cystic hydatid disease is an infection caused by the larval stage of a cestode parasite called Echinococcus granulosus. Hydatid cysts are one of the major parasitic infections in Libya that causes many health problems to human and responsible for economic losses because of the condemnation of the slaughtered animals infected viscera as well as reducing the quality and quantity of the livestock other productions such as milk, wool and meat. Many abattoir investigations in Libya have revealed that, cystic hydati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Meta-analysis revealed that, the estimated pooled prevalence of CE among livestock in countries of Arabia Peninsula during a period of 21 years, from June 2000 to June 2021, was 13.4%(95% Cl:10.9-16.0). These results are in agreement with findings reported by Vaisi-Raygani et al [15] in Iran, who reported the pooled prevalence rate as 13.9% (95% CI: 10.7-17.7%), and lower than prevalence rate (53.5%) reported by Ibrahem et al [62] in Libya. The differences in the prevalence rate of CE among various studies could be due to climatic conditions, which could affect the viability of parasite's eggs, infected final hosts and livestock farming system in region and level of contact with dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Meta-analysis revealed that, the estimated pooled prevalence of CE among livestock in countries of Arabia Peninsula during a period of 21 years, from June 2000 to June 2021, was 13.4%(95% Cl:10.9-16.0). These results are in agreement with findings reported by Vaisi-Raygani et al [15] in Iran, who reported the pooled prevalence rate as 13.9% (95% CI: 10.7-17.7%), and lower than prevalence rate (53.5%) reported by Ibrahem et al [62] in Libya. The differences in the prevalence rate of CE among various studies could be due to climatic conditions, which could affect the viability of parasite's eggs, infected final hosts and livestock farming system in region and level of contact with dogs.…”
Section: Discussionsupporting
confidence: 93%
“…This lesion corresponds to a larval, inoculable, non-contagious cestodosis common to humans and to various animal species. It is due to the development in the body (particularly in the liver or the lungs) of vesicular larvae of the Echinococcus type of parasites living in the adult state in the small intestine of carnivores [ 11 ]. There are various species; the most important being Echinococcus granulosus .…”
Section: Discussionmentioning
confidence: 99%
“…Untreated water from sources such as lakes may also contain Echinococcus eggs and should therefore, be avoided. Unfortunately, over the past decades, there has been no CE control programme in Libya, but the high incidence of the disease in humans (1.4 to 2%) (Shambesh et al, 1999), and the high prevalence of hydatidosis in livestock, which has been reported to be 1.6 to 40% in sheep, 5.6 to 70% in goats, 2.7 to 56% in cattle, and 2.7 to 48% in camels (Ibrahem et al, 2016), suggests the need for an extensive control programme.…”
Section: Mohamed Et Almentioning
confidence: 99%